Strong trade-offs characterise water-energy-food related sustainable development goals in the Ganges–Brahmaputra–Meghna River basin. (1st October 2022) - Siderius, Christian; van Walsum, Paul; Biemans, Hester
Abstract: The United Nations' sustainable development goals (SDGs) set ambitious policy targets for 2030 to overcome poverty while preserving the planet. These goals are not perfectly aligned; trade-offs emerge during implementation at regional and local levels, such as in a river basin. Here, we quantify important trade-offs between water, energy, and food-related SDGs in the Ganges–Brahmaputra–Meghna River basin, a climate vulnerability hotspot, using multi-objective optimisation based on detailed water resources and crop production modelling and accounting for uncertainties in the costs of water, labour, and land. The trade-off between food production and agricultural profit is strong; the amount of people fed would be reduced by more than two-thirds, were profitability maximized. However, we do see the potential to achieve higher profitability in agriculture against limited loss of food and hydropower production and limited impact on downstream environmental flows, although continued reliance on groundwater and energy, currently unsustainable, needs to be mitigated.